Investigating the potential of an alternative export route for fresh fruit produced in the Northern Provinces of South Africa : the case for the Port of Maputo - De Bod, Anja Mari (Stellenbosch : Stellenbosch University, 2025)
Thesis (MCom)--Stellenbosch University, 2025.